2016
DOI: 10.3847/0004-637x/820/1/54
|View full text |Cite
|
Sign up to set email alerts
|

Grain Size Constraints on Hl Tau With Polarization Signature

Abstract: The millimeter-wave polarization of the protoplanetary disk around HL Tau has been interpreted as the emission from elongated dust grains aligned with the magnetic field in the disk. However, the self-scattering of thermal dust emission may also explain the observed millimeter-wave polarization. In this paper, we report a modeling of the millimeter-wave polarization of the HL Tau disk with the self-polarization. Dust grains are assumed to be spherical and to have a power-law size distribution. We change the ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
149
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(161 citation statements)
references
References 63 publications
11
149
1
Order By: Relevance
“…These new observations are enabling not only studies of polarization at the scale of protoplanetary disks (where the polarization may be due to a combination of thermal dust emission and scattering: see Kataoka et al 2015Kataoka et al , 2016aYang et al 2016b,a) but are also producing magnetic field maps with far more independent polarization detections across each individual source. These latter maps can be used to study the interplay between magnetic fields and turbulence in low-mass star-forming cores; because of limited image sensitivities, previous interferometric studies have mainly focused on high-mass star-forming regions (e.g., Houde et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These new observations are enabling not only studies of polarization at the scale of protoplanetary disks (where the polarization may be due to a combination of thermal dust emission and scattering: see Kataoka et al 2015Kataoka et al , 2016aYang et al 2016b,a) but are also producing magnetic field maps with far more independent polarization detections across each individual source. These latter maps can be used to study the interplay between magnetic fields and turbulence in low-mass star-forming cores; because of limited image sensitivities, previous interferometric studies have mainly focused on high-mass star-forming regions (e.g., Houde et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A radial magnetic field pattern is derived from an azimuthal polarization pattern, assuming that the polarization arises from magnetically aligned dust grains (i.e., the magnetic field orientations are perpendicular to the polarization orientations, as was assumed in Figures 1 and 2 and described in Section 1). However, an azimuthal polarization pattern can also arise from self-scattering of dust emission from a face-on (or slightly inclined) protoplanetary disk: recent theoretical work has shown that, depending on the combination of dust density, dust-grain growth, optical depth, disk inclination, and resolution of observations, polarization from scattering in disks could contribute to the polarized emission at millimeter wavelengths, perhaps even eclipsing the signal from magnetically aligned dust grains (Kataoka et al 2015(Kataoka et al , 2016aPohl et al 2016;Yang et al 2016aYang et al , 2016bYang et al , 2017. There is now potential evidence for this dust scattering effect from ALMA observations (Kataoka et al 2016b); other high-resolution polarization observations by CARMA and the Karl G. Jansky Very Large Array (VLA; Stephens et al 2014;Cox et al 2015;Fernández-López et al 2016) may also be consistent with self-scattered dust emission.…”
Section: Gravitational Infall or Dust Scatteringmentioning
confidence: 99%
“…This prediction can readily be tested with ALMA observations. ALMA polarization data is available for the transition disk HD 142527 (Kataoka et al 2016a), although its interpretation is complicated by the intrinsic asymmetry in the dust distribution. In any case, the observed pattern does not contradict in any obvious way the expectation that the large millimeter-emitting grains have settled in this evolved disk, although more detailed modeling is required to draw a firmer conclusion.…”
Section: Evolution Of Dust Settling From Polarization Of Inclined Disksmentioning
confidence: 99%
“…Such a config-uration would produce a polarization pattern that appears inconsistent with the pattern observed in HL Tau (Stephens et al 2014). The apparent inconsistency led Yang et al (2016a) to propose that the disk polarization in HL Tau comes from dust scattering, based on Kataoka et al (2015) theory of scattering-induced millimeter polarization (see also Kataoka et al 2016a). Specifically, they show that dust scattering in a disk inclined to the line of sight can naturally explain why the observed polarization vectors are roughly parallel to the minor axis and the distribution of polarized intensity is elongated along the major axis.…”
Section: Introductionmentioning
confidence: 99%